Factors Influencing Brain Healthy Diets Among Older Midwestern African Americans. (17th December 2021) - Shaw, Ashley; Fikru, Samantha; Berkley-Patton, Jannette; Goode, Chris; Perales, Jaime; Vidoni, Eric
Abstract: Emerging evidence suggests that up to half of Alzheimer's disease (AD) cases are a result of modifiable risk factors related to poor diet such as blood pressure and diabetes, disproportionately affecting African Americans. Adherence to brain healthy diets remains low among African Americans. Therefore, it is important to understand needs, preferences, and barriers to inform intervention designs aimed to reduce AD risk among African Americans. Using a qualitative community-based research approach, we conducted six semi-structured focus group discussions (n= 30) to explore older African American experiences with brain healthy diets, preferences, and barriers to eating healthy. Secondly, we assessed the feasibility and acceptability of collecting biomarkers of health status and dietary behaviors among African Americans. A thematic analysis was conducted to identify emerging themes and biomarkers of health status were analyzed using descriptive statistics. We identified four themes: "Knowledge and Beliefs about Brain Healthy Diets, " "Eating Practices, " "Ways to Improve Dietary Practices, " and "Preferences for Enhancing Awareness about Brain Healthy Diets." Themes indicated that older African Americans are receptive to healthy dietary consumption but perceived lack of education, cost, access, and perception of losing one's culture as barriers to adherence. A total of 87.5% of participants completed biomarker assessments and 82% tested positive for 1 or more cardiovascular risk factor. Our study identified ways to enhance brain healthy dietary practices to reduce dementia risk. Also, our study demonstrated feasibility and acceptability in collecting AD related biomarkers in the African American community.